Legal Analysis of Digital Donation Campaigns: A Case Study of Agus Salim's Donation Compliance and Accountability Based on the Minister of Social Affairs Regulation Number 8 of 2021 - Khuan, Hendri; Sopian, Sopian (West Science Law and Human Rights, 2025)
This study examines the compliance and accountability of the Agus Salim digital donation campaign about Minister of Social Affairs Regulation Number 8 of 2021. Employing a normative juridical approach, the research analyzes legal provisions and evaluates the campaign's adherence to regulatory requirements, focusing on permit acquisition, transparency, and reporting obligations. The findings reveal partial compliance, highlighting challenges such as delayed permit approval, insufficient financial transparency, and gaps in reporting mechanisms. The study also identifies limitations in the regulatory framework, including enforcement difficulties and the absence of digital-specific guidelines. These results underscore the need for revised regulations and enhanced accountability measures to ensure the ethical and effective operation of digital donation campaigns in Indonesia.